Pelatihan Komputer Guna Meningkatkan Pengetahuan Siswa Madrasah Ibtidaiyah - Toni; Feti Fatonah; Suse Lamtiar; Johan Wahyudi; Sabdo Purnomo (Politeknik Penerbangan Indonesia Curug, 2021)
MI Mathla”ul Huda is a private school under the auspices of the Ministry of Religion with the school education degree AHO-0019782.AH.01.04.2016A. At MI Mathla’ul Huda , some of the students are orphaned and underprivileged children. Given the opportunity to go to school like other children free of charge they still pay only for textbook uniforms even though the condition are what they are. School continue to strive to educate the lives of the nation’s children. In order to increase knowledge of their students, school conditions have not been supported by adequate infrastructure, one of which is the unavailability of a computer lab. Of course with these conditions, children will learn only in theory and the results will not be as optimal if they can directly practice community service carried out by the Indonesian Aviation Polytechnic Curug is one of the media that connects the word of education with the surrounding community, in order to provide benefits to the community around PPIC is an aviation polytechnic located in legok District, Tangerang Regency, in terms of community service activities it is necessary to take part in the program to educate the nations children around the campus, this is not only a form of higher education Tridharma, but also as a real manifestation of PPIC’s concern in improving human resources for underprivileged people around the campus. Again with the conditions of the covid pandemic disaster as it is today, the PPIC leaders can participate more. By carrying out computer training activities for children at MI Mathlaul Huda.